FUTURE GLOBAL EDUCATION LANDSCAPE SHAPED BY DESIGN, NOT BY CHANCE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KARNATAKA, INDIA, 18 November 2016 Transforming the Malaysian educational landscape to prepare for future generations of Malaysians would need to be by design and no longer by chance.